2011
DOI: 10.1158/1078-0432.ccr-11-0430
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Dose Escalation, Pharmacokinetic, and Pharmacodynamic Evaluation of eIF-4E Antisense Oligonucleotide LY2275796 in Patients with Advanced Cancer

Abstract: Purpose The antisense oligonucleotide, LY2275796, blocks expression of eIF-4E, an mRNA translation regulator upregulated in tumors. This Phase I study sought an appropriate LY2275796 dose in patients with advanced tumors. Experimental Design A 3-day loading dose, then weekly maintenance doses, were given to 1–3 patient cohorts, beginning with 100 mg and escalating. Plasma samples were collected to determine LY2275796 concentrations; tumor biopsies, to quantify eIF-4E mRNA/protein. Results Thirty patients w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 16 publications
3
91
1
Order By: Relevance
“…It is believed that antitumor effects with 4EASO would be enhanced in combination with chemotherapy or radiation. 29 The results presented here demonstrate that 4EASO potently sensitizes NSCLC cells to gemcitabine and support the notion of enhanced chemosensitivity with 4EASO in NSCLC. With this in mind, 4EASO is being examined for the treatment of patients with stage IV non-small-cell lung cancer NSCLC in combination with chemotherapy in phase I/II trials.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It is believed that antitumor effects with 4EASO would be enhanced in combination with chemotherapy or radiation. 29 The results presented here demonstrate that 4EASO potently sensitizes NSCLC cells to gemcitabine and support the notion of enhanced chemosensitivity with 4EASO in NSCLC. With this in mind, 4EASO is being examined for the treatment of patients with stage IV non-small-cell lung cancer NSCLC in combination with chemotherapy in phase I/II trials.…”
Section: Discussionsupporting
confidence: 80%
“…27 A phase 1 clinical trial of 4EASO (LY2275796) in advanced human cancer was carried out owing to the promising findings from these preclinical investigations and the results recently published. 29 The maximum tolerated dose and biological effective dose of 1000 mg 4EASO was determined employing a dose escalation experimental design. When comparing pre-and posttreatment tumor biopsies, a decrease in eIF4E expression was observed in the majority of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I clinical trial showed reduction of eIF4E protein by up to 65% by an antisense oligonucleotide (LY2275796) in most of the 30 patients tested (43). Other targets of eIFs include PI3K and mTOR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…a phase 1 trial, of the 30 patients who received at least 1 dose of the eIF4E antisense oligonucleotide, 7 patients had stable disease of at least 6 weeks duration and 2 patients had disease control for over 3 months. 31 Other efforts have included the use of the ribavirin, an antiviral drug that may mimic the m 7 G cap to block eIF4E activity. 27 A clinical trial of ribavirin was conducted in patients with AML, and among the 11 evaluable patients, there was 1 complete remission and 2 partial remissions.…”
Section: Discussionmentioning
confidence: 99%